Wastewater Purification from Permanganate Ions by Sorption on the Ocimum basilicum Leaves Powder Modified by Zinc Chloride - Nasser A. Alamrani; Hatem A. Al-Aoh; Meshari M. H. Aljohani; Suhair A. Bani-Atta; M. Sobhi; Mustafa Syed Khalid; A. A. A. Darwish; Ali A. Keshk; Mona A. A. Abdelfattah (Journal of Chemistry)
The powder of Ocimum Basilicum leaves was treated by zinc chloride (ZnCl2) and applied as a new and low-cost sorbent for extraction of permanganate anions (MnO4−) from liquid phase. The functional groups of the ring stretching vibration, –NH2 deformation, stretching of C-O, stretching of CH, and stretching of –NH were found in the sorbent of zinc chloride Ocimum basilicum leaves powder (ZCOBLP) at 1516.21, 1629.33, 1047.00, 2929.88, and 3294.93 cm−1, respectively. This adsorbent has 8.3 pHZPC, 117.27 m2·g−1 surface area, 0.00711 cc·g−1 pore volume and average pore diameter of 264.144 Å. The outcomes of sorption experiments designate the positive impact for temperature, time of agitation, and started concentration of MnO4− and negative impact for pH. The optimal conditions were 1300 mg·L−1 as started adsorbate concentration, 55°C as solution temperature, agitation time of 420 min, and pH of 1.5. The outcomes of the equilibrium and dynamic approve that this sorption is spontaneous and heat-absorbing process, and the obtained data were described well by isotherm model of Langmuir and 2nd-order dynamic model. The capacities of this sorption were 588.235, 625.000, 666.667, and 714.286 mg·g−1 at 25, 35, 45, and 55 (°C), respectively. The superior sorption capacities of the uncostly ZCOBLP will make it successfully used for MnO4− ions extraction from liquid phases.